(untitled) (Research, Society and Development, 2021)
Hand Hygiene (HH) is a simple and essential action in the prevention of infectious diseases. Therefore, the aim of this study was to evaluate the levels of adherence, technique, and knowledge about HH by healthcare workers and perform an educational intervention. We conducted a cross-sectional analysis with 20 professionals, for six months. We observed and categorized the HH opportunities, evaluated the performance of the correct technique, determined the degree of HH compliance (Positivity Index proposed by Carter, IPC) and applied a questionnaire about HH. The data contributed to conduct training and discussion about COVID-19, using a didactic model of virus. We observed N = 791 opportunities for HH, but only N = 128 (16.18%) were performed, with the correct technique in 80.47% (N = 103). The categories with the greatest number of opportunities for HH were “after patient care” (N = 238) and “before patient care” (N = 214). However, HH occurred only in N = 76 (31.93%) and N = 28 (13.08%), respectively. Comparing the categories, the highest adherence was "after removing the gloves" (53.19%). The degree of HH compliance in this study is lower than that recommended by the IPC (70%). In the questionnaires, workers affirmed to have taken at least one course about HH throughout their careers; few of them mentioned virus as a microbe present in the hands; “Lack of time” was the major reason to not HH. The educational intervention reinforced the importance of the correct HH technique, stimulated adaptations in the hospital structure and in strategies for coping with the emergence of the pandemic.